STRATEGI GURU DALAM MEMBELAJARKAN MATEMATIKA PADA MATERI LINGKARAN KEPADA ANAK TUNAGRAHITA (Studi Kasus pada Siswa Kelas VIII SLB Muhammadiyah Cepu) - Utami, Anita Dewi; Sujadi, Imam; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2014)
Abstract: The aim of this study was to describe teacher?s strategy in teaching mathematics on the topic of circle to intellectual disability students in SLB Muhammadiyah Cepu. The subject of this study was classroom mathematics teacher and all students of eighth grade of SLB Muhammadiyah Cepu. The data of this study was teacher?s strategy in teaching mathematics on the topic of circle taken from the result of recording transcription of teaching and learning process through two observations. The data validity technique used in this study was member check, a process of data checking taken by the researcher from the subject of the study to examine the possibilities of different assumptions. The result reveal that in opening activity (pre-activity) and closing activity (post-activity), teacher implemented movement and rhythm strategy by asking the students to sing circle song. While in the main activity, teacher?s strategy in teaching mathematics on the topic of circle was dealing with conceptual knowledge by implementing Bruner?s learning theory at enactive stage, it is by introducing the concept of the form of circle with some learning media to students. Then, the teacher?s strategy in teaching mathematics on the topic of circle which deals with procedural knowledge was by implementating guided discovery model, it is by guiding the students to do activity to count the circle?s circumference by using thread. But, because of the limitation of the mentally handicapped students? intellectuality, the guided discovery model which was implemented by the teacher was firstly by giving some examples to the students, then asking the students to practice to find the circle?s circumference from the length of the thread by the students themselves.Keywords: teacher?s strategy, conceptual knowledge, procedural knowledge, mathematics teaching learning, student with intellectual disability.